(untitled) (Annual of the Faculty of Philosophy in Skopje, 2010)
This paper is aimed at explaining the nature, patterns, history, stages and possible intermediaries of money laundering as an aspect of organized crime. This paper also has discussed the negative impact of money laundering on the national security system of Republic of Macedonia as well as the current international initiatives against it with a view to assessing the future potentials for an effective global enforcement. Global responses to the challenges of money laundering could be in the form of raising awareness about the phenomenon, especially its socioeconomic impact; creating the necessary legal and institutional frameworks; and of course, effective law enforcement and fostering international cooperation.